2017
DOI: 10.3892/mmr.2017.7287
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Bu Zhong Yi Qi decoction on simulated weightlessness-induced muscle atrophy and its mechanisms

Abstract: Microgravity has been previously demonstrated to induce skeletal muscle atrophy, loss of muscle force and disorders in myogenesis and metabolism. Current pharmacological strategies exhibit poor efficacy. Bu Zhong Yi Qi decoction (BZ) is a well-known traditional Chinese medicine decoction used for myasthenia gravis. In the present study, its effect on unloading induced muscle atrophy was investigated. The mousetail suspension model was used to simulate weightlessness induced muscle atrophy. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…In Cho SG et al, the combination of Schisandra chinensis Baill, Lycium chinense Mill, and Eucommia ulmoides Oliv inhibited muscular atrophy and increased muscle strength and cross-sectional area of muscle fiber [36]. Zhu M et al also reported the similar effects on muscular atrophy by using Bu Zhong Yi Qi decoction [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cho SG et al, the combination of Schisandra chinensis Baill, Lycium chinense Mill, and Eucommia ulmoides Oliv inhibited muscular atrophy and increased muscle strength and cross-sectional area of muscle fiber [36]. Zhu M et al also reported the similar effects on muscular atrophy by using Bu Zhong Yi Qi decoction [37].…”
Section: Resultsmentioning
confidence: 99%
“…LE enhanced those proteins and also activated the PI3K-Akt/mTOR signaling pathway [34]. In Zhu M. et al, the results indicated that Bu Zhong Yi Qi decoction (BZ) significantly downregulated NCoR1 expression and further induced muscle differentiation and metabolism by regulating NCoR1-associated gene expression [37].…”
Section: Resultsmentioning
confidence: 99%
“…The report also showed the multiple effects of medicinal plants on ischemic stroke including the protective role and recovery against injury [ 65 ]. Buzhong Yiqi is a herbal formula used for treating various conditions [ 66 ] such as muscle atrophy, whereby the decoction can downregulate nuclear receptor corepressor 1 and its downstream factors [ 67 ]. Mitochondrial oxidative metabolism was identified as the mechanism underlying the Buzhong Yiqi-mediated recovery of muscle quantity [ 67 ].…”
Section: Pharmacological Action Of Plants Tested Using In Vivo Andmentioning
confidence: 99%
“…Buzhong Yiqi is a herbal formula used for treating various conditions [ 66 ] such as muscle atrophy, whereby the decoction can downregulate nuclear receptor corepressor 1 and its downstream factors [ 67 ]. Mitochondrial oxidative metabolism was identified as the mechanism underlying the Buzhong Yiqi-mediated recovery of muscle quantity [ 67 ]. Furthermore, the therapeutic mechanism underlying Shufeng Jiedu comprises eight medicinal herbs, and AKT1 kinase was considered as a key factor in acute lung injury [ 68 ].…”
Section: Pharmacological Action Of Plants Tested Using In Vivo Andmentioning
confidence: 99%
“…Qi-deficiency symptoms include shortness of breath, lassitude, listlessness, spontaneous sweating, a pale tongue, and a weak pulse [ 1 ]. Many related single or complex formulas have been widely prescribed in TCM to ameliorate these symptoms [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%